Reproductive biology of the neotropical rattlesnake Crotalus durissus from northeastern Brazil: A test of phylogenetic conservatism of reproductive patterns - Barros, Verônica Alberto [UNESP]; Sueiro, Leticia Ruiz; Almeida-Santos, Selma Maria [UNESP] (My University, 2012)
We studied reproductive patterns in neotropical rattlesnakes (Crotalus durissus) from areas with different climatic conditions. The timing of female reproductive events (vitellogenesis, sperm storage and parturition) was identical in both regions, therefore we assume it to be phylogenetically conserved. However, size at maturation in both sexes and male reproductive cycles (timing of spermatogenesis and testicular regression) was markedly different between study areas, suggesting that these reproductive characteristics widely differ across the species' range.
Keywords: Long-term sperm storage; Reproductive cycles; Spermatogenesis